Proceedings of International Conference on Soft Computing Techniques and Engineering Application ICSCTEA 2013, September 25-27, 2013, Kunming, China - Patnaik, Srikanta; Li, Xiaolong; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2014)
The main objective of ICSCTEA 2013 is to provide a platform for researchers, engineers and academicians from all over the world to present their research results and development activities in soft computing techniques and engineering application. This conference provides opportunities for them to exchange new ideas and application experiences face to face, to establish business or research relations and to find global partners for future collaboration.
Research on Hierarchical Clustering Algorithm based on Cluster Outline -- Exploration of Fault Diagnosis Technology for Air Compressor-Based on Internet of Things -- An Enhancement Algorithm Based on Fuzzy Sets Algorithm using Computer Vision System for Chip Image Processing -- Development of DDoS Attack Defense System Based on IKEv2 Protocol -- Power Data Network Dynamic Simulation Platform -- An Emotional Model based on Multiple Factors -- Multi-source and Heterogeneous Knowledge Organization and Representation for Knowledge Fusion in Cloud Manufacturing -- Research of Dynamics and Deploying Control Method of Tethered Satellite -- Using Auto Associative Neural Networks for Signal Recognition Technology on Sky Screen -- Research on the Hotspot Information Push System for the Online Journal based on Open Source Framework -- Development of Control System of Wheel Type Backhoe Loader -- Some results on fuzzy weak Boolean filters of non-commutative residuated lattice -- CGPS: A Collaborative Game in Parking Lot Search -- A Fuzzy-Based Context-aware Privacy Preserving Scheme For Mobile Computing Services -- Research and Application of Trust Management System -- Ranaad-Xek-A Prototype Design of Traditional Thai Musical Instrument Application for Android Tablet PC -- Identifying Accurate Refactoring Opportunities Using Metrics -- Research on Neural Network Predictive Control of Induction Motor Servo System for Robot -- Research on Scale-out Workloads and Optimal Design of Multicore Processors -- Study of Modified Montgomery's Algorithm and Its Application to 1024-bit RSA -- A MVS-based Object-relational Model of the Internet of Things -- Rateless Codes Based Unequal Loss Protection for Layer-coded Media Delivery -- Construction of the Grade-3 System for GJB5000A-2008 -- Virtual Training System of Assembly and Disassembly based on Petri Net -- The Design of Visual RBAC Model based on UML and XACML Integrating -- A New Approach to Reproduce Traffic Accident based on the Data of Vehicle Video Recorders -- Improved RNS Montgomery modular multiplication with residue recovery -- Functionally Equivalent C Code Clone Refactoring by Combining Static Analysis with Dynamic Testing -- Architecture Designing of Astronaut Onboard Training System based on AR Technology -- Design and Implementation of Bibliometrics System based on RIA -- SAR Image Filtering based on Quantum-inspired Estimation of Speckle Variance -- Image Semantic Annotation Approach based on the Feature Matching -- Research on Transmission and Transformation Land Reclamation based on BP Neural Network -- TTP-ACE: A Trusted Third Party for Auditing in Cloud Environment -- Pattern Recognition based on the Nonparametric Kernel Regression Method in A-share Market -- The Research on the Detection and Defense Method of the Smurf Type DDos Attack -- A Preliminary Analysis of Web Usage Behaviors from Web Access Log Files-A Case Study of Prince of Songkla University, Thailand -- Assessment of BER Performance of a Power Line Communication System in the Presence of Transformer and Performance Improvement Using Diversity Reception -- A Multi-constraint Anonymous Parameter Design Method Based on the Attribute Significance of Rough Set -- Design and Implementation of a Middleware for Service-Oriented Distributed Systems -- Refactoring Structure Semantics Similar Clones Combining Standardization with Metrics -- A Retail Outlets Classification Model Based on Adaboost -- Extensions of Statecharts with Time of Transition, Time Delay of Message Transmitting, and Arrival Probability of Message -- The Optimization of Hadoop Scheduling Algorithms on Distributed System for Processing Traffic Information -- Understanding the Capacity Scaling of Personal Communications Services -- VHDL Implementation of Complex Number Multiplier Using Vedic Mathematics -- Key Security Technologies of Cloud Computing Platforms -- The Measurement and Analysis of Software Engineering Risk based on Information Entropy -- GRACE: A Gradient Distance based Peer-to-Peer Network Supporting Efficient Content-based Retrieval -- Image Denoising Using Discrete Orthonormal S-transform -- Analyzing Services Composition Using Petri Nets -- FPGA-based Image Processing for Seamless Tiled Display System -- 2D Simulation of Static Interface States in GaN HEMT with AlN/GaN super-Lattice as Barrier Layer -- Study on Model and Platform Architecture of Cloud Manufacturing for Aerospace Conglomerate -- Services Composition Algorithm for Vehicle Network Based on Multiple Ontology -- Design and Application of Virtual Laboratory For Photography -- The Research of Travel-time Tomography Based on Forward calculation and Inversion -- Protein Secondary Structure Prediction based on Improved C-SVM for Unbalanced Datasets -- An Algorithm for Speckle Noise based on SVD and QSF -- A Generation Model of Function Call Based on the Control Flow Graph -- A Novel Community-based Trust Model for P2P Networks -- The Algorithm of Mining Frequent Itemsets based on MapReduce -- Multi-Feature Metric Guided Mesh Simplification -- Research of Medical Image Fusion Algorithms based on Nonsubsampled Contourlet -- Influence of Previous Cueing Validity on Gaze-Evoked Attention Orienting -- Application of RBF Neural Network in Intelligent Fault Diagnosis System -- An Analysis of the Keys to the Executable Domain-Specific Model.
Keywords: Computer science; Data mining; Artificial intelligence; Telecommunication; Computer Science; Artificial Intelligence (incl. Robotics).; Data Mining and Knowledge Discovery; Communications Engineering, Networks